The synthesis of the 2,3-difluorobutan-1,4-diol diastereomers - Szpera, Robert; Kovalenko, Nadia; Natarajan, Kalaiselvi; Paillard, Nina; Linclau, Bruno (Beilstein Journal of Organic Chemistry, 2017)
The diastereoselective synthesis of fluorinated building blocks that contain chiral fluorine substituents is of interest. Here we describe optimisation efforts in the synthesis of anti-2,3-difluorobutane-1,4-diol, as well as the synthesis of the corresponding syn-diastereomer. Both targets were synthesised using an epoxide opening strategy.
Keywords: acetal isomerization; deoxyfluorination; epoxide opening; fluorinated building block; vicinal difluoride